Pedestal structure, stability and scalings in JET-ILW: the EUROfusion JET-ILW pedestal database. (23rd November 2020) - Frassinetti, L.; Saarelma, S.; Verdoolaege, G.; Groth, M.; Hillesheim, J.C.; Bilkova, P.; Bohm, P.; Dunne, M.; Fridström, R.; Giovannozzi, E.; Imbeaux, F.; Labit, B.; et al.
Abstract: The EUROfusion JET-ILW pedestal database is described, with emphasis on three main issues. First, the technical aspects are introduced, including a description of the data selection, the datasets, the diagnostics used, the experimental and theoretical methods implemented and the main definitions. Second, the JET-ILW pedestal structure and stability are described. In particular, the work describes the links between the engineering parameters (power, gas and divertor configuration) and the disagreement with the peeling-ballooning (PB) model implemented with ideal magnetohydrodynamics equations. Specifically, the work clarifies why the JET-ILW pedestal tends to be far from the PB boundary at high gas and high power, showing that a universal threshold in power and gas cannot be found but that the relative shift (the distance between the position of the pedestal density and of the pedestal temperature) plays a key role. These links are then used to achieve an empirical explanation of the behavior of the JET-ILW pedestal pressure with gas, power and divertor configuration. Third, the pedestal database is used to revise the scaling law of the pedestal stored energy. The work shows a reasonable agreement with the earlier Cordey scaling in terms of plasma current and triangularity dependence, but highlights some differences in terms of power and isotope mass dependence.